Effect of aging on the microstructures and mechanical properties of AZ80 and ZK60 wrought magnesium alloys - Wu Y.J.; Zhang Z.M.; Li B.C. (Science of Sintering, 2010)
In this paper, the effects of solution and aging on the microstructures and mechanical properties of AZ80 and ZK60 wrought magnesium alloys are investigated by optical microscope, electronic scanning microscope and mechanical testers. The result shows that both the tensile strength and elongation of AZ80 alloy increase firstly and then decrease with the increasing of the aging temperature, the peak values appear when the aging temperature is 170°C. The hardness of ZK60 alloy increases firstly and then decreases with the increasing of the aging temperature, and the hardness reaches its peak value at 170°C. However, the toughness of the alloy is just the opposite. Moreover, ZK60 alloy has good performances in both impact toughness and other properties at the aging temperature from 140 to 200°C.